2022
DOI: 10.1111/and.14538
|View full text |Cite
|
Sign up to set email alerts
|

Co‐overexpression of VEGF and Smad7 improved the therapeutic effects of adipose‐derived stem cells on neurogenic erectile dysfunction in the rat model

Abstract: Cavernous nerve injury is the main cause of erectile dysfunction (ED) after radical prostatectomy (RP). In our previous study, injection of adipose-derived stem cells (ADSCs) into the cavernosum can repair damaged cavernosum nerves and ED can be restored to a certain extent. In order to improve these therapeutic effects, we evaluated the efficacy of ADSCs co-modified with VEGF and Smad7 in a rat model. SD rats were randomly divided into six groups: a sham surgery group, and the five bilateral cavernous nerve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Some studies published in 2022 used modifications in stem cell preparation or co-interventions aiming to enhance their therapeutic effect. He et al evaluated the efficacy of ADSC co-modified with VEGF and Smad7 in a CNI rat model [ 42 ]. Erectile function in rats treated with co-modified ADSC was more distinctly recovered.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies published in 2022 used modifications in stem cell preparation or co-interventions aiming to enhance their therapeutic effect. He et al evaluated the efficacy of ADSC co-modified with VEGF and Smad7 in a CNI rat model [ 42 ]. Erectile function in rats treated with co-modified ADSC was more distinctly recovered.…”
Section: Resultsmentioning
confidence: 99%
“…After sorting, we developed five general study categories, such as adipose-derived stem cells (ADSCs), mesenchymal stem cells (MSCs), urine-derived stem cells (USCs), placental stem cells (PSCs), muscle-derived stem cells (MDSCs). Here, only some of the most representative papers are listed as shown in Table 1 [ 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 ].…”
Section: Preclinical Research Of Ed Biotherapymentioning
confidence: 99%
“…For ADSCs-based ED treatment, He et al [ 10 ] showed that injection of extracted ADSCs from the bilateral groin area can repair damaged corpus cavernosum nerves and restore ED to a certain extent, while injections of ADSCs modified by overexpression of VEGF and Smad7 can prevent penile fibrosis, reduce collagen deposition, and improve relaxation properties of smooth muscle cells, thereby restoring erectile function in bilateral cavernous nerve injury (BCNI)-induced ED rats. In addition, Zhang et al [ 11 ] and Cheng et al [ 12 ] also isolated ADSCs from epididymal adipose tissues and human adipose tissues [ 11 13 14 ], and these isolated ADSCs can also restore erectile function in different ED models, such as type 1 diabetic, neurotic, and age-associated ED.…”
Section: Preclinical Research Of Ed Biotherapymentioning
confidence: 99%